2022
DOI: 10.3389/fvets.2021.812922
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement Equivalence Study of the Family Bondedness Scale: Measurement Equivalence Between Cat and Dog Owners

Abstract: About 38.4% of U.S. households include a dog, and 25.4% a cat, as pets, and a recent poll suggested over 90% of pet owners feel their companion animal is a family member. Numerous studies have suggested pet ownership has physical, mental, and social health benefits, though much of this research has yielded mixed results. Results of a recent review suggested significant measurement problems in human-animal interaction (HAI) and human-animal bond (HAB) research, including the absence of validity evidence, overly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…to the vets, is more challenging for all parties [ 39 ]. Another explanation may be the different levels of attachment that owners have towards dogs and cats, as the majority of studies show that dog owners are more strongly attached to their dogs than cat owners are to their cats [ 16 , 41 , 42 ], which may influence their willingness to seek veterinary care for them. A recent paper by our group [ 37 ] based on data from the same survey as the present paper found that in general cat owners were less willing to spend larger sums of money on veterinary care for their cats than dog owners were willing to spend on their dogs, although major cross-country differences were noted.…”
Section: Discussionmentioning
confidence: 99%
“…to the vets, is more challenging for all parties [ 39 ]. Another explanation may be the different levels of attachment that owners have towards dogs and cats, as the majority of studies show that dog owners are more strongly attached to their dogs than cat owners are to their cats [ 16 , 41 , 42 ], which may influence their willingness to seek veterinary care for them. A recent paper by our group [ 37 ] based on data from the same survey as the present paper found that in general cat owners were less willing to spend larger sums of money on veterinary care for their cats than dog owners were willing to spend on their dogs, although major cross-country differences were noted.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The number of pets has increased in households worldwide, ranging from 38% to 68% in the European Union and the United States, with 25% of the population owning cats, 25% to 38% owning dogs, and up to 90% of pet owners considering their companion animal a part of their family. 8,9 Not surprisingly, many families facing a diagnosis of chronic disease compensate their children for the related setbacks by acquiring a pet. 10 A number of studies have suggested that animal-assisted therapies (AATs) can be beneficial for patients, [11][12][13] given that animal contact can exert beneficial effects in terms of physical, mental, and social health for children and adults with chronic medical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…10 A number of studies have suggested that animal-assisted therapies (AATs) can be beneficial for patients, [11][12][13] given that animal contact can exert beneficial effects in terms of physical, mental, and social health for children and adults with chronic medical conditions. [6][7][8]11 These benefits might even be greater in the case of immunocompromised patients who, because of compulsory isolation, are especially vulnerable to emotional discomfort. Half of adult lung transplant recipients own pets, 14 as do two thirds of children with chronic diseases such as cancer and diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations